Clinical Outcome of High Tibial Osteotomy by Hemicallotasis Using a Dynamic Axial Fixator on 52 Knees - Anand Kumar Gupta; Debojyoti Mukherjee; Sanjay Kumar (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: Osteoarthritis (OA) is the major cause of osteoarticular disability in the elderly population. The knee is the most commonly affected joint, and replacement surgeries are the main modality of treatment in advanced cases. Whereas in unicompartmental disease especially in relatively younger age groups, joint preserving surgeries are preferred. The aim of the present study was to evaluate the functional outcome of graduated open wedge high tibial osteotomy (HTO) in patients with OA of the knee with <65 years of age. Methods: HTO through medial open wedge technique was done in 48 patients (52 knees) and stabilized by limb reconstruction system. Distraction was started at the 7th day at the rate of 1 mm/day and continued till proper alignment was achieved. The clinical outcome of patients has been calculated on the basis of anatomical correction and functional improvement. Anatomical correction was determined on the basis of a radiological criterion (Hip-Knee-Ankle [HKA] angle) on the scanogram. Whereas, the functional outcomes of the patients were measured on Oxford Knee Score (OKS) and Western Ontario and McMaster Universities OA Index (WOMAC) score scales. Results: The valgus correction in varus knees of patients were achieved by gain in mean HKA angle (increase by 11° ±0.9°). The desired range of correction in HKA angle was seen at the final follow-up of 41 out of 52 knees (78.8%). There was undercorrection in 4 knees (7.7%) and overcorrection in 7 (13.4%) knees. All the functional scores showed significant improvement in the postoperative scores. There was a positive correlation between the HKA angle with OKS and WOMAC Score. The most common complication was superficial pin tract infection, which was seen in 7 (13.4%) patients. Conclusions: HTO by unilateral external fixator produces good clinical outcomes and also has its added benefits. It is less invasive, no internal hardware present, and safer in terms of neurovascular complications.